Left ventricular hypertrophy patterns in hypertensive subjects with chronic kidney disease - Zhemanyuk, S. P.; Syvolap, V. V.; Lukashenko, L. V.; Жеманюк, Світлана Павлівна; Сиволап, Віталій Вікторович; Лукашенко, Ланна Віталіївна (My University, 2024)
The aim of the study was to analyze LV hypertensive patterns in adult individuals with arterial hypertension and CKD.
Keywords: тези доповідей